Pengembangan dan Pengenalan Kaos “Ndlodok” Endymion Screen Printing Melalui Promosi - Kasnowo Kasnowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The creative industry is an industry that focuses on the creation and exploitation of intellectually owned works, one of which is fashion design, including t-shirts. The current condition of society, both individuals and groups, are now starting to build their brands with the innovation and creativity they build, including Ndlodok T-shirts. This community service is the second stage, namely to introduce ndlodok t-shirts to the community. The initial offer of the